Some Biochemical Markers in Type 1 Diabetes Patients - Abdul adheem, Dhifaf; Abdallah Hassan, Ekhlas (ASJ - Academic Science Journal, 2025)
Type 1 diabetes mellitus (T1DM) is characterized by hyperglycaemia in combination with biochemical changes in glucose, lipid profile and glycated haemoglobin (HbA1c). This study aims to assess glucose, lipid profile, glycated haemoglobin (HbA1c), UREA and Creatinine in type 1 diabetic subjects. Type 1 patients were selected from the subjects attending National Center of Diabetes (AL- Mustansiria University) the number of patients are 90 the number of male are 47 the number of female are 43. Fasting blood sugar (FBS), lipid profile were determined by enzymatic methods, glycated haemoglobin (HbA1c) was measured by (HPLC), UREA and Creatinine (by kinetic method) in patients were compared with healthy controls there number are 30.  type 1 diabetic patients showed statistically significant increase in the levels of HbA1c, urea, creatinine , FBS, total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), whereas statistically significant decreased level was found in triglycerides (TGs) and very low- density lipoprotein(VLDL). In addition, HDL/LDL ratio were significantly higher than the control subject was.  In conclusion: There are associated biological vulnerabilities to type 1 diabetes compare to the control subjects. Further research is warranted to quantify the magnitude of complications and confirm their observation in clinical populations.